Communication skills of practicing pharmacists and pharmacy students. - M. Majzub, Rohaty; M. Rais, Maisarah; Jusoff, Kamaruzaman (Canadian Research & Development Centre of Sciences and Cultures, 2010)
Communication skills are of utmost importance to both students and practicing pharmacists. In order to become successful pharmacists, one needs to possess excellent communication skills to serve the clients. This study examined the perception of 1st year pharmacy students who are currently enrolled in a course entitled Communication Skills for Pharmacy. A sample of 21 students was identified through purposive sampling. They were examined on a) the importance of communication skills in ESP and b) their perceived abilities on the selected communication skills. In addition, 21 practicing pharmacists were interviewed through interview protocols regarding similar issues. The pharmacy students were also involved in a focus group interview technique to gain insights into their communication skills. The preliminary findings showed that whilst the majority of students rated most communication skills as very important, the results also indicated that they perceived having both moderate and lesser abilities in executing such skills. A comparison with practicing pharmacists indicated that the latter have greater abilities to practice communication skills in their daily professional lives. The latter also highlighted that good communication skills has enabled them to (a) prescribe drugs aptly (b) empathize with the clients frame of mind (c) sustain networking with their clients. The findings have practical and educational implications in practicum, curriculum and career development of pharmacists. Keywords: communication skill; practicing pharmacist; pharmacy student.